2018
DOI: 10.17148/iarjset.2018.594
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of The Effect of Motivation, Job Satisfaction, and Organizational Commitment on Performance

Abstract: Human resources have a major role in every organizational activity. The resources of the organization will not provide optimal results if it is not supported by human resources who have a capable performance. To achieve good performance, performance variable cannot stand alone. This means that there are several supporting variables that can affect performance variable. Work motivation, Job Satisfaction, and Organizational Commitment are three variables that have an influence on improving employee performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 7 publications
2
9
1
Order By: Relevance
“…This finding is also consistent with earlier studies indicating organizational commitment as a psychosocial mechanism that may link the relationship between motivation and job performance [ 40 , 41 ]. Also, this finding is not also consistent with Widarto and Anindita's study [ 42 ] where they found that there was no mediate effect in the relationship. These findings reveal a strong positive correlation between achievement motivation and job performance in physicians, which corroborates with the results from previous studies [ 43 ].…”
Section: Discussioncontrasting
confidence: 69%
“…This finding is also consistent with earlier studies indicating organizational commitment as a psychosocial mechanism that may link the relationship between motivation and job performance [ 40 , 41 ]. Also, this finding is not also consistent with Widarto and Anindita's study [ 42 ] where they found that there was no mediate effect in the relationship. These findings reveal a strong positive correlation between achievement motivation and job performance in physicians, which corroborates with the results from previous studies [ 43 ].…”
Section: Discussioncontrasting
confidence: 69%
“…The study results state that there is a significant positive effect of motivation on organizational commitment. This means that it is consistent with previous studies' results (Zeglat et al, 2017;Foroudi et al, 2018;Widarto & Anindita, 2018). Thus, management must have the courage to take strategic policies to prevent many employees from resigning.…”
Section: Structural Modelsupporting
confidence: 91%
“…Various surveys with different respondents also show the same thing. In other words, there is a correlation between job satisfaction and job performance, with high job satisfaction leading to better performance for employees (Widarto & Anindita, 2018;Ramli, 2019;Sidabutar et al, 2020;Nurdiansyah et al, 2020;Imran et al, 2020;Ridlwan et al, 2021). Thus, this study formulates the following hypothesis:…”
Section: Relationship Of Job Satisfaction and Job Performancementioning
confidence: 90%